The case for genetically modified crops with a poverty focus - Atkinson, Howard J.; Green, Jayne; Cowgill, Sue; Levesley, Aurora (Trends in biotechnology (Regular ed.), 2001)
Recently seven National Academies of Science produced a report on transgenic plants and world agriculture. The report provides scientific perspectives to the ongoing public debate about the potential role for transgenic technology in world agriculture. In this article, we develop the themes of the report and emphasize the potential for future genetically modified (GM) crops with a poverty focus, emphasizing the potential of GM resistance to plant parasitic nematodes for subsistence potato farmers in Bolivia. We judge that a range of incremental gains to crop yields from many transgenes are valuable for future world security. We advocate the establishment of a standard that GM crops must achieve before they are both biosafe and appropriate for resource-poor farmers and we believe that the best interests of the poor require biotechnologists to work towards that objective.